Prevalence human papillomavirus type 6 and type 11 in pregnant women - Haruna, Nadyah; Hatta, Mochammad; Hamid, Firdaus; Sultan, Andi Rofian; Safri, Safri; Farid, Monika Fitria; Lestari, Esa (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: Pregnancy reduces the effectiveness of cell-mediated immunity, making the body more vulnerable to Human Papilloma Virus (HPV) infection. HPV comes in multiple variants, including non-pro-oncogenic varieties like 6 and 11. Less research has been done on low-risk HPV infections than on high-risk HPV since they are more frequently linked to genital warts and rarely result in cancer. Examples of these infections are types 6 and 11. It is necessary to conduct this study to ascertain whether asymptomatic pregnant women have been exposed to HPV types 6 and 11.Purpose: This study aims to determine prevalence HPV types 6 and 11 in pregnant women.Methods: A descriptive cross-sectional survey was carried out in Makassar in May 2023. The study Population consisted of pregnant women who underwent antenatal care at Tajuddin Chalid Hospital Makassar during the specified research period. After providing clarification and obtaining consent from eligible mothers, we collected a swab from the vaginal area. A PCR examination was conducted on the 167 maternal swabs that were received. Statistical analyses included frequency distribution using SPSS.Results: According to the study, 121 (72.5%) of the 167 samples tested positive for HPV type 6 DNA, while 46 (27.5%) tested negative. Meanwhile, 67% of 167 patients tested positive for HPV type 11 but were negative for the virus. Only 21 respondents with negative identification were found to be harboring both low-risk Human Papillomavirus types. In addition, 78 respondents received positive results for HPV types 6 and 11.Conclusion: Pregnant women can be infected with HPV types 6 and 11 even if they are asymptomatic. The high percentage of positive results suggests that routine maternal screening is recommended, especially during pregnancy.